TO ESTIMATE THE INCIDENCE OF POTENTIAL DRUG-DRUG INTERACTION IN STROKE PATIENTS ADMITTED IN A TERTIARY CARE HOSPITAL, TELANGANA - FIRDOUS, SIDRAH; AWAD, SAFA AMREEN SALIM; FATIMA, AFIFA; AHMED, MOHAMMAD FARHAN; ANITHA, N.; ALI, NILOUFER (International Journal of Current Pharmaceutical Research, 2020)
Objective: To determine the frequency and pattern of potential drug-drug interactions in hospitalized stroke patients. Methods: A retrospective study was carried out among patients treated for ischemic and haemorrhagic stroke at a tertiary care hospital, Hyderabad for a period of 1 y. A total of 177 prescriptions were analyzed during the study period. The potential drug-drug interactions were identified using Clinirex software. Results: Among the 177 prescriptions, 63.8% were male and 36.2% were female. Out of 177, 79 % of prescriptions had shown potential drug-drug interactions. The patients prescribed with more than 5 drugs developed higher incidence of drug-drug interactions. Based on severity scale we observed 12% major, 71% moderate and 17% minor drug-drug interactions. The incidence of pharmacodynamic interactions was 68% and the pharmacokinetic interactions were 32%. Conclusion: This study suggests that patients with stroke are frequently exposed to potential drug-drug interactions. The incidence of potential drug-drug interactions was higher in patients above 40 y. Most of the prescriptions contained polypharmacy which may lead to increased risk of hospitalization and higher health care cost. It is essential to identify potential drug-drug interactions especially in elderly patients as early as possible in order to prevent adverse drug reactions and ensure patient’s safety.